2016
DOI: 10.1007/s00445-016-1013-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the host-substrate properties on maar-diatreme volcanoes: experimental evidence

Abstract: While the relationship between the host-substrate properties and the formation of maar-diatreme volcanoes have been investigated in the past, it remains poorly understood. In order to establish the effects of the qualitative host-substrate properties on crater depth, diameter, morphological features and subsurface structures, we present a comparison of four campaigns of experiments that used small chemical explosives buried in various geological media to simulate the formation of maar-diatremes. Previous resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Goto et al (2001) observed that the crater diameter (D) increased with explosion energy according to = 0.32 − 2.06, (88) and Sato and Taniguchi (1997) found that the relationship between the diameter and the volume of ejecta (V) was = 0.97 0.36 (89) and that 0.7-10% of the initial thermal energy was converted into kinetic energy. Strong host materials favored higher crater rims as well as larger and deeper craters with steep walls (Macorps et al 2016). Multiple explosions, typical of phreatomagmatic eruptions, created craters of about the same size as that of individual events of similar energy but that were narrower and deeper (Valentine et al 2012).…”
Section: Phreatomagmatic and Hydrothermal Eruptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Goto et al (2001) observed that the crater diameter (D) increased with explosion energy according to = 0.32 − 2.06, (88) and Sato and Taniguchi (1997) found that the relationship between the diameter and the volume of ejecta (V) was = 0.97 0.36 (89) and that 0.7-10% of the initial thermal energy was converted into kinetic energy. Strong host materials favored higher crater rims as well as larger and deeper craters with steep walls (Macorps et al 2016). Multiple explosions, typical of phreatomagmatic eruptions, created craters of about the same size as that of individual events of similar energy but that were narrower and deeper (Valentine et al 2012).…”
Section: Phreatomagmatic and Hydrothermal Eruptionsmentioning
confidence: 99%
“…For a given explosion energy the optimal depth was defined as that resulting in the maximum crater diameter. With granular materials, a negligible amount of energy was consumed to fragment the host medium, unless it had some significant strength (Macorps et al 2016), in contrast to natural cases that involve coherent rocks. Experiments showed that explosions generated jets whose height was set by the normalized depth and which also controlled the distribution of ejecta from shallow levels outside (Graettinger et al 2014).…”
Section: Phreatomagmatic and Hydrothermal Eruptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In soft substrates, maar-diatreme volcanoes tend to have large and bowlshaped craters, with gently dipping inner walls [91]. Recent analog experiments as well as field observations from classical diatremes cut into "soft substrate" showed that the diatreme wall can be steep for such maars that cut through soft substrate (e.g., [121][122][123][124][125]). This might be valid for the geometry of the upper part of the maar-diatreme volcano, especially for its crater, given that the number of individual eruptions can also heavily affect the final crater-diatreme morphology, and as many explosive events take place hence as large and old as your maar, the role of the substrate physical conditions will be reduced (e.g., [125]).…”
Section: Features Of Complex Maar Volcanoesmentioning
confidence: 99%
“…Recent analog experiments as well as field observations from classical diatremes cut into "soft substrate" showed that the diatreme wall can be steep for such maars that cut through soft substrate (e.g., [121][122][123][124][125]). This might be valid for the geometry of the upper part of the maar-diatreme volcano, especially for its crater, given that the number of individual eruptions can also heavily affect the final crater-diatreme morphology, and as many explosive events take place hence as large and old as your maar, the role of the substrate physical conditions will be reduced (e.g., [125]). In contrast, maars formed in hard-rock environment tend to be irregular, small in size and characterized by funnel-shaped and vertical (e.g., Joya Honda, Mexico [126], Nyos Maar, Cameroon [127]) to steeply dipping crater walls.…”
Section: Features Of Complex Maar Volcanoesmentioning
confidence: 99%